Influence of the Stresses σ5 and σ6 and the Electric Field E1 on the Thermodynamic Parameters of GPI Ferroelectric - Vdovych, A.S.; Zachek, I.R.; Levitskii, R.R. (Ukrainian Journal of Physics, 2021)
Effects arising in glycine phosphite (GPI) ferroelectrics under the action of the shear stresses q5 and q6 and the electric field E1 have been studied in the framework of a modified model that accounts for the piezoelectric coupling between the ordered structural elements and the strains